Risk factors for anesthesia failure in the mandible. (International Journal of Medical and Surgical Sciences, 2017)
Local anesthesia is a common procedure in the daily dental practice, however, there are multiple factors affecting the effectiveness of this procedure. Correct identification of the causes of the failure is essential at the time of taking the necessary measures to achieve the anesthetic success. Most problems in the anesthesia of the mandible are due to limited access and anatomical variants, such as: bifid Inferior Alveolar Nerve, Retromolar Foramen, Accessory Mental Foramen, Accessory innervations and Cross Innervations. Moreover, inflammation increases the absorption of anesthetic, reducing its concentration at the site of action. The several techniques available for mandibular anesthesia does not guarantee 100% effectiveness, plus each individual techniques presents indications and complications. Psychological phenomena such as anxiety and fear to the dentist can also increase the perception of pain. The clinician should all aspects involved but also the psychological variables that negatively affect dental patient care in anesthetic procedures.
Keywords: Anesthesia; dental; third; molar; anatomic; variation; fear; pain